2009
DOI: 10.3844/ajassp.2009.882.887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Dexmedetomidine versus Fentanyl to Intrathecal Bupivacaine on Spinal Block Characteristics in Gynecological Procedures: A Double Blind Controlled Study

Abstract: Problem statement:The purpose of this study was to evaluate the onset and duration of sensory and motor block as well as operative analgesia and adverse effects of Dex Metedo Midine (DXM) or fentanyl given intrathecally with plain 0.5% bupivacaine for spinal anesthesia. Approach: seventy six patients classified as American Society of Anesthesiologists (ASA) status I, II and III scheduled for vaginal hysterectomy, vaginal wall repair and tension free vaginal tape were prospectively studied. Patients were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
128
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 33 publications
17
128
1
Order By: Relevance
“…Use of dexmedetomidine as an adjuvant mixed with local anaesthetics has been performed with neuraxial anesthesia in both adult and paediatric patients [17,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of dexmedetomidine as an adjuvant mixed with local anaesthetics has been performed with neuraxial anesthesia in both adult and paediatric patients [17,27].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is still under evaluation as an ideal neuraxial adjuvant as it provides stable hemodynamic conditions, good quality of intraoperative and prolonged postoperative analgesia with minimal side effects [16][17][18]. Kanazi et al, demonstrated a significant prolongation in the duration of sensory and motor block with dexmedetomidine used as intrathecal additive for 0.5% heavy bupivacaine [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 In other studies, it was observed that addition of various doses of clonidine to bupivacaine intrathecally significantly prolongs duration of analgesia of bupivacaine, 16,27,28 while others reported that addition of dexmedetomidine to bupivacaine significantly prolongs the duration sensory and motor block and post-operative analgesia. 23,25,[29][30][31] …”
Section: Discussionmentioning
confidence: 99%
“…23 The sedation effect of α2 agonist is postulated to be in the locus ceruleus (a bilateral nucleus that contains many adrenergic receptors) in the brainstem. The locus ceruleus is also the origination site for the descending medullospinal adrenergic pathway, which is known to be a key mechanism in regulating nociceptive neurotransmission.…”
Section: Discussionmentioning
confidence: 99%